Analysis Organoleptik Eco Enzim From Organic Waste Based on Fruits and Vegetables - Ismail, Agus Yadi; Adhya, Ilham; Hendrayana, Yayan; Nurdin, Nurdin; Nurlaila, Ai; Herlina, Nina; Kosasih, Dede; Dzulfannazhir, Fauzan; Sofyan, Hadiyan Nur; Aminudin, Sukron (Universitas PGRI Semarang, 2023)
Waste processing, especially organic waste, which in practice is still not optimal in Indonesia. One method of processing organic waste is using eco enzymes, which are made by fermenting vegetable and fruit waste combined with water and sugar. The raw materials for making eco enzymes vary and have different characteristics so they have high potential to be used in various fields. This research aims to examine the properties of organoleptic eco enzymes their raw materials and their application to human requirements. This study used an experimental method by repeating twice for each raw material including vegetables, a mixture of fruit peels (mango, pineapple, durian), pineapple peel, banana peel, and orange peel. Then the eco enzyme data is analyzed for characteristics based on parameters such as color, aroma, taste, and pH. According to the findings, the eco enzyme has a distinct brown color that ranges from light brown to dark brown, the aroma and taste produced show from very sour and smelly to a slightly sour and characteristic smell, and than the pH levels range from 2.98 to 3.50. The characteristics that have been analyzed organoleptic in this study indicate that the eco enzymes produced are very good, namely brown color, sour aroma, slightly doormat taste, and a pH value of 4. Eco enzymes are used in various fields such as household needs as cleaning fluids, the environment as a wastewater purifier, health is used to improve well water quality, and agriculture as a fertilizer and plant disinfectants